The development of heterogeneous catalyst C/CaO/NaOH from waste of green mussel shell (Perna varidis) for biodiesel synthesis. Issue 5 (October 2017) - Hadiyanto, H.; Afianti, Asha Herda; Navi'a, Ulul Ilma; Adetya, Nais Pinta; Widayat, W.; Sutanto, Heri
Abstract: This study was aimed to use green mussel shell ( Perna viridis ) as raw materials for CaO heterogeneous catalyst in the transesterification process of palm oil into biodiesel. Green mussel shell was calcined for 3 h at a temperature of 900 °C to become CaO catalyst, then mixed by activated carbon with the ratio of C:CaO = 2:3 and impregnated with a solution of NaOH. The catalyst was used in biodiesel production at constant reaction temperature of 65 °C for 3 h and methanol to oil ratio of 0.5:1 (%wt). The optimum yield biodiesel was 95.12%, which was achieved at NaOH concentration at impregnation process of 30% and the catalyst load of 7.5%. The obtained biodiesel properties were in agreement with national standard (SNI) of biodiesel.